(untitled) (Phenomenology, Humanities and Sciences, 2025)
The paper deals with the broad relationship between perception and language in the work of Merleau-Ponty, using a key interpretive approach: the distinction between animality and humanity, which also unfolds throughout his work. We begin here with Merleau-Ponty’s description of perceptual and verbal forms (Gestalten) to consider them as products of internal differentiation processes. 1) At the perceptual level, differentiation is based on distinctive valences within the field (in hyletic or sensory data that function in a diacritical manner), without the need to stabilize a single reference. This level extends to the entirety of animal signals and codes. 2) At the linguistic level, differentiation operates in structural equivalences (already with diacritical signs), progressing toward proper reference or, in phenomenological language, toward the “thing itself.” Ultimately, it is possible to understand both the unity and diversity among beings through these processes, bringing to light the specificity of the human being as a “referential animal,” without, however, severing its deep connection with the totality of beings, in what Merleau-Ponty refers to as “flesh” in his later writings.